PENGARUH METODE BERCERITA TERHADAP PERKEMBANGAN ANAK USIA DINI: STUDI LITERATUR - Ali Sadikin; Marhamah (Jurnal Pendidikan Nusantara, 2024)
Early childhood represents a formative period that shapes the trajectory of language, cognition, socio-emotional competence, moral character, motor skills, and creativity. Learning approaches during this period must therefore be attuned to how young children naturally grow and learn. Storytelling is one instructional approach widely applied in early childhood education, functioning not merely as entertainment but as a pedagogical device that sharpens listening skills, enlarges vocabulary, stimulates imagination, and instills moral character through meaningful narratives. This article synthesizes published research on the influence of storytelling on early childhood development using a literature-review design, drawing on secondary sources such as journal articles, books, and conference proceedings that were gathered through documentation and examined through content analysis. The synthesis indicates that storytelling consistently contributes to gains in language, listening, cognition, socio-emotional competence, creativity, and moral character, with its effectiveness shaped by the teacher's delivery, the media employed, the suitability of material to the child's developmental stage, and the teacher's active engagement throughout the lesson. Storytelling therefore stands out as a workable instructional strategy for accelerating early childhood development.